Effect of intraoperative mannitol administration on acute kidney injury after robot-assisted laparoscopic radical prostatectomy: A propensity score matching analysis. Issue 26 (June 2018) - Kong, Yu-Gyeong; Park, Ji Hyun; Park, Jun-Young; Yu, Jihion; Lee, Joonho; Park, Se-Ung; Jeong, In Gab; Hwang, Jai-Hyun; Kim, Hee Yeong; Kim, Young-Kug
Abstract : Abstract: Mannitol, an osmotic diuretic, has been used to prevent acute kidney injury (AKI). However, studies have found divergent effects of intraoperative mannitol administration on postoperative AKI. We therefore evaluated the effects of intraoperative mannitol administration on AKI after robot-assisted laparoscopic radical prostatectomy (RALP) in prostate cancer patients. A total of 864 patients who underwent RALP were divided into mannitol (administered at 0.5 g/kg) and no-mannitol groups. Demographics, cancer-related data, preoperative laboratory values, intraoperative data, and postoperative outcomes such as AKI, chronic kidney disease at 12 months postoperation, duration of hospital stay, and intensive care unit admission rate and duration of stay were compared between the 2 groups using propensity score matching analysis. To determine the risk factors for AKI after RALP, univariate and multivariate logistic regression analyses were performed. Postoperative AKI was defined according to the Kidney Disease: Improving Global Outcomes criteria. After performing 1:1 propensity score matching, the mannitol and no-mannitol groups included 234 patients each. The overall incidence of AKI after RALP was 5.1% and was not significantly different between the no-mannitol and mannitol groups in the propensity score-matched patients (13 [5.6%] vs. 11 [4.7%], P = .832). Univariate logistic regression analysis revealed that body mass index and operative time were associated with AKI in 864 patients who underwent RALP. However, intraoperative mannitol administration was not associated with AKI after RALP ( P = .284). Multivariate logistic regression analysis revealed that operative time was significantly associated with AKI after RALP (odds ratio = 1.013, P = .001). The incidence of chronic kidney disease (13 [5.6%] vs. 12 [5.1%], P = 1.000) and other postoperative outcomes were not also significantly different between the no-mannitol and mannitol groups in the propensity score-matched patients. Intraoperative mannitol administration has no beneficial effect on the prevention of AKI after RALP in prostate cancer patients. This result provides useful information for clinical practice guidelines regarding intraoperative mannitol use.